Traffic Counting Location and Error Bound in Origin-Destination Matrix Estimation Problems - Gan, Liping; Yang, Hai; Wong, Sze Chun (Journal of transportation engineering, 2005)
Estimating origin-destination trip matrices from link traffic counts has been a subject of substantial research. It is well known that the accuracy of the resulting estimated origin-destination (O-D) matrix largely depends on the employed estimation approach itself, errors of the input data, and an appropriate set of links from which flow information should be collected. Previous studies have overwhelmingly focused on the development of various estimation models, while paying very limited attention to the traffic counting location and error bound issues. Recognizing their interdependence, this study makes a joint investigation of the traffic counting location, estimation method, and error bound in an integrated manner, while taking into account the effects of various route choice assumptions made in the traffic assignment models and the levels of traffic congestion on the network. A few useful properties of the counting location rules and error bound measures for the O-D matrix estimation problem are demonstrated theoretically and numerically.